(untitled) (Global Journal of Management and Business Research, 2013)
Labor markets of Turkey are characterized by low female labor force participation when compared with the OECD, neighbour states and EU averages. Besides, the female labor force participation exhibits an unexplained and suprising declining trend in the last decades. The paper attemps to illuminate the phenomenon searching for contingencies in data presented by working women in a microfinance clientele survey in suburban Ankara, especially focusing on status and family related interrelationships that could provide explanation for the low relative number of working women in labor markets of Turkey, testing the Under-participation trap hypothesis.